Peran Brand Image Dalam Memediasi Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Lipstick Wardah : (Survei Pada Mahasiswi Program Studi Manajemen Universitas Perjuangan Tasikmalaya) - Nindia Fadilla Ramadhanti (CV. ULIL ALBAB CORP, 2022)
One of the growing businesses in Indonesia today is a cosmetic company. This study aims to determine product quality, brand image, and purchasing decisions of wardah lipsticks, the effect of product quality on purchasing decisions of wardah lipsticks, the role of brand image in mediating product quality on purchasing decisions of wardah lipsticks. This research was conducted at the University of Struggle Tasikmalaya with a sample of 236 students of the Management study program at the University of Struggle Tasikmalaya class of 2018-2021. Samples were obtained through purposive sampling technique with the calculation of the Slovin formula. The research method used in this research is causality method with survey approach as quantitative research. The results of this study indicate that the type of Wardah lipstick product that is most trusted as a quality product and has a brand image on the students of the Management Study Program, Universitas Perjuangan Tasikmalaya is Exclusive Matte Lipstick. Brand Image is able to mediate the relationship between product quality and purchasing decisions as evidenced by the results of the Sobel test which shows the z value obtained is > 1.96 with a significance level of 5%, which is 4.447.